(untitled) (Vietnam Journal of Community Medicine, 2026)
Background/Objectives: Monitoring medical incidents helps identify underlying causes and propose improvement measures to enhance hospital management quality and ensure patient safety. This study aimed to describe the characteristics of medical incidents occurring at Viet Tiep Friendship Hospital branch 2 - An Dong , in 2024. Methods: A cross-sectional descriptive study was conducted by analyzing 736 medical incident reports recorded at Viet Tiep Friendship Hospital branch 2 - An Dong, from January 1 to December 31, 2024. Results: In 2024, 100% of medical incidents were recorded and reported through the electronic reporting system. Medical incidents occurred most frequently on Tuesdays and Wednesdays, accounting for 22.1% and 20.8%, respectively. Incidents related to technical procedures and professional interventions constituted high proportion with 31.7%. A total of 70.8% of incidents resulted in increased resource utilization for patient care. The primary contributing factor was staff-related causes (65%). Conclusions: Regular monitoring and periodic evaluation of medical incidents are essential for proposing appropriate interventions, thereby improving hospital management quality and ensuring patient safety.